Perlindungan Hukum Indikasi Geografis terhadap Makanan Khas "Lemang Batok" Tebing Tinggi sebagai Produk Lokal: (Studi Kasus Persepsi Pelaku Usaha Lemang Batok Tebing Tinggi) - Parlaungan Gabriel Siahaan; Santi Theresia Sinurat; Sri Muallimah; Lisa Alfira Andini; Vebri Meliarni Oktavia (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This Mini Research Report is titled "Legal Protection of Geographical Indications for Typical Foods of Lemang Batok Tebing Tinggi as Local Products." This study examines the understanding of business actors, the forms of legal protection available, and the role of local governments in the Geographical Indication (GI) registration process. The research utilizes a descriptive qualitative approach, employing interviews as the primary data collection technique, and data analysis through methods such as data reduction, data display, and data verification. The findings indicate that business actors, although they do not fully understand the concept of Geographical Indications, continue to preserve the authenticity of their production methods and pass them down through generations. However, the local government's involvement in the GI registration process is still limited, resulting in a lack of legal protection for this local product. The study highlights the need for increased awareness and involvement from both business actors and local authorities to strengthen the legal protection for Lemang Batok Tebing Tinggi as a unique geographical product. It concludes by emphasizing the importance of implementing effective strategies to safeguard such products and ensure their recognition in the legal domain.